Receiver-Oriented 'Pull' Model For ResettaNet Trade Documents Interchange. - Ting, Tin Tin; Khoo, Vincent, Kay Teong (2007)
A major challenge in integrating trading partners' processes is effective document interchange. Traditional business-to-business (B2B) process integration is based on a 'Push' model through which documents are pushed from the senders to the receivers, as in emailing and electronic data interchange.